Building an Integrative Framework for Change Management for Digital Transformation in Public Services - Samsodin, Samsodin (Asian Digital Governance Problems, 2026)
Purpose: This study aims to conceptually examine prominent change management models and evaluate their relevance for supporting digital transformation in public sector organizations. Subjects and Methods: The research applies a literature review approach by analyzing academic articles, books, and best-practice reports. The data were examined using thematic analysis involving reduction, categorization, and synthesis to identify the strengths, limitations, and gaps in the application of Lewin’s Three-Step Model, ADKAR, Kotter’s Eight-Step Model, and Beer and Nohria’s Theory E and Theory O. Results: The review indicates that no single framework can universally address the complexity of digital change in the public sector. Lewin’s model contributes to building organizational readiness, ADKAR focuses on individual engagement and capability, Kotter underlines the importance of leadership and vision, while Theory E and Theory O stress balancing structural performance and cultural development. Evidence from transformation experiences in Microsoft and Kodak confirms that leadership commitment, organizational culture, and employee preparedness are decisive factors. Conclusions: An integrative approach that combines complementary elements from multiple models is more suitable for achieving sustainable digital transformation and improving governance outcomes in public service institutions.